APPLICATION OF THE POLYGRAPH UNDER THE CONDITIONS OF MARITAL STATE IN UKRAINE - Zdebskyi, Dmytro (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
B a c k g r o u n d . Choosing the most effective polygraph methods to meet the needs of military and law enforcement forces in Ukraine, in the conditions of martial law, determined the relevance of our subject. The adaptation of the best international standards of research using the polygraph and the development of a great national school, taking into account the psychological features of the polygraph practice, is an up-to-date requirement on the way to European integration, successful struggle with the Russian occupation forces and countering internal threats. At the same time, in psychological science, the use of the polygraph in accordance with the modern challenges of war has not been researched enough.M e t h o d s . A complex of research methods was applied, including: theoretical (analysis, comparison, synthesis of theoretical and methodological approaches to research results), empirical (observation, survey, testing, experiment), methods of statistical processing of research data (actual analysis and comparison of samples). To assess the reliability of the statements of the interviewees, the survey used the method of pretest interview according to the Federal system, the method of the test of test questions – "Federal Zone Comparison Test" (Federal ZCT) for constructing test questions and "Empirical Scoring System – Multinominal" (ESS-M) for evaluating the received results.R e s u l t s . A ranking of effectiveness was carried out, according to the importance of each of the psychophysiological channels in polygraph examinations. The data obtained by us were compared with a meta-analytic study of the American Polygraph Association (APA). The obtained results made it possible to identify the criteria and indicators of the effectiveness of the polygraph in the conditions of martial law in Ukraine, taking into account certain psychological indicators of military personnel.C o n c l u s i o n s . In accordance with the results of the study, based on the identified psychological indicators, the conditions for the effectiveness of the polygraph in official checks and investigations conducted in the military units of Ukraine under martial law were established and confirmed. The effectiveness of the application of polygraph methods was confirmed by comparison with the APA meta-analysis. The results of the obtained data provided an opportunity to refute the version regarding the incompatibility of the American methods of polygraph examinations with the mentality of the citizens of Ukraine.
Keywords: correspondence of American methods of polygraph research to the mentality of Ukrainian citizens, Empirical Scoring System – Multinominal, effectiveness of polygraph use in the conditions of martial law in Ukraine, official checks and investigations with the use of polygraph, Federal zone comparison test